2019
DOI: 10.3390/ani9090684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partial Replacement of Conventional with Alternative Feeds on Nutrient Intake, Digestibility, Milk Yield and Composition of Awassi Ewes and Lambs

Abstract: Simple SummaryAlternative feeds have been used to feed animals for decades by replacing traditional feeds to increase the profit of raising livestock. In this study, alternative feeds (dried distillers grains with solubles, carob pods, olive cake, and bread by-product) were fed to Awassi ewes and ewe lambs at 0, 200, and 400 g/kg. Chemical composition was similar among diets. Feed intake, body weight change, and milk yield did not differ among diets. Cost of milk production decreased in alternative feeds conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…In agreement with previous studies dealing with alternative feedstuffs (Obeidat 2018(Obeidat , 2020Aloueedat et al 2019;Hatamleh and Obeidat 2019), the cost of diets diminished by 20 and 24% in the OC and ATR diets, respectively, compared to the CON diet. These findings could be due to the fact that the cost of alternative feeds is cheaper than that of conventional feeds.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies dealing with alternative feedstuffs (Obeidat 2018(Obeidat , 2020Aloueedat et al 2019;Hatamleh and Obeidat 2019), the cost of diets diminished by 20 and 24% in the OC and ATR diets, respectively, compared to the CON diet. These findings could be due to the fact that the cost of alternative feeds is cheaper than that of conventional feeds.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this critical period requires a well-balanced diet, which in general is considered very costly. To solve this problem, livestock producers have started to depend on alternative feeds as part of the diet [14], due to their price and good availability [15]. Consistent with the current study, no health problems were observed in other studies conducted in our laboratory using different alternative feeds (sesame meal, olive cake, bread by-products, dried distillers' grains with solubles, carob pods, Atriplex halimus L.) [14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
“…To solve this problem, livestock producers have started to depend on alternative feeds as part of the diet [14], due to their price and good availability [15]. Consistent with the current study, no health problems were observed in other studies conducted in our laboratory using different alternative feeds (sesame meal, olive cake, bread by-products, dried distillers' grains with solubles, carob pods, Atriplex halimus L.) [14][15][16][17]. Overall the nutrient content in the BCM (such as the CP and EE; Table 1) indicates how this ingredient to be used as an alternative feed.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, as the amount of DDGS used in feed is increased, the cost of the feed is reduced. Previous studies conducted in our laboratory have produced similar results in studies where conventional feeds were replaced by alternative feeds, indicating the beneficial use of DDGS in ruminant diets [1,6,12].…”
Section: Discussionsupporting
confidence: 64%